A Study on the Artistic Characteristics of Mongolian Folk Song Regional Styles: (Based on Materials from barga buryat and chakhar, uzemchin in Inner Mongolia) - SH, WULIJIBAYAER; U, WENDULA (Studia Folclorica, 2025)
While the study of Mongolian folk songs (Urtyn duu) has progressed significantly in Inner Mongolia, there remains a lack of thorough research evaluating the creative characteristics of clan and tribal melodic styles. This research aims to conduct a comparative examination of the artistic attributes in the folk songs of the Barga-Buryat and Uzemchin-Chakhar. The findings have significant scientific implications for the study of Mongolian folk songs and broader Mongolian studies. This study employs a fresh methodological framework to examine the Five Pentatonic Modes Theory of the Orient as well as ethnomusicological recording methodologies. It examines established attributes such as melodic structure patterns, critical aspects of melodic quality, important sections of phrase-final vowels, essential features of phrase lengthening strategies, key elements of melodic conventions, and major segments of professional singing styles. Монгол уртын дууны бүс нутгийн уран сайхны шинж чанарын судалгаа (Өвөр Монголын барга буриад, цахар үзэмчний баримтуудаар) Хураангуй: БНХАУ-ын ӨМӨЗО-ын монгол уртын дууны судлал хөгжиж ирсэн боловч овог аймгийн айд ая аялгууны уран сайхны шинж чанарыг гүнзгийрүүлэн судалсан бүтээл олон харагдахгүй байна. Тус өгүүлэлд барга, буриад болон үзэмчин, цахрын уртын дууны уран сайхны шинж чанарыг харьцуулан судалсан үр дүнг танилцуулав. Энэ нь монгол уртын дуу, цаашилбал монгол судлалд шинжлэх ухааны чухал ач холбогдол өгөх юм. Судалгааны арга зүйн хувьд, дорно дахины таван эгшигт хөгжмийн онолд үндэслэн, үндэстний дуу хөгжмийн бүртгэл судалгааны аргыг ашиглан, эдгээр уртын дууны хөгийн цомнол, хөгийн чанарын үндсэн шинж, өгүүлбэрийн төгсгөлийн эгшиг, өгүүлбэрийн төгсгөлийн уртатгал, аялгууны хэв намба, дуулах арга барилын шинж чанар гэх мэт хэвшмэл мөн чанарт дүн шинжилгээ хийснээрээ шинэлэг талтай. Түлхүүр үг: Өвөр Монгол, Барга, Буриад, Цахар Үзэмчин, Уртын дуу, Уран сайхны шинж чанар, Дуулах хэв маяг